Pengaruh Stock Split Terhadap Harga Saham dan Volume Perdagangan Saham Perusahaan Go Public di Bursa Efek Indonesia Tahun 2012 - Asrani Dewi; Lestari Wuryanti (Universitas Malahayati, 2014)
Abstract. Stock split policy can be interpreted as an act of splitting a share of stock into n pieces. The stock split resulted in the increase in the number of shares outstanding without the sales transaction that alter the amount of capital. Price per new shares after the stock split is equal to 1 / n of the stock price before splitting. Condition of the company influence on prices and trading volumes. Therefore, this study examined the effects of 10 days before and after the stock split on stock prices and trading volume of shares in companies that go public on the Stock Exchange in 2012, with jumlag sample of 12 companies that Petrosa, Tbk, Pakuwon Jati Tbk, Astra International , Tbk, Astra International, Tbk, Modern Internasional, Tbk, Centra Omega Resources, Tbk Kresna Graha Sekurindo, Tbk, Indosiar Karya Media Tbk, Kalbe Farma Tbk, Surya Citra Media Tbk, Ace Hardware Indonesia, Tbk Berlina, Tbk. The results of tests conducted is just the Petroza Tbk PT affords results that there is an influence of dilakukannnya stock split on stock prices. While the 11 other companies tudak no influence. the calculation results paired samples t-test trading volume of shares of 12 companies showed that the stock price 10 price of the day after the stock split and the 10 days prior to the stock split has decreased different, when viewed from the goal stock split is expected to increase the volume of trading shares in a company. The average trading volume of 12 companies undergo changes varying magnitude after the stock split. A total of eight companies experienced an increase in trading volume, while four other companies decreased stock trading.